"Análisis, diseño e implementación de un sistema para el manejo de inventario y gestión alimenticia del hospital del instituto ecuatoriano de seguridad social (IESS) de la ciudad de Machala. Módulo: Gestión alimenticia de los pacientes y sistema para la elaboración y planificación de menú para el departamento de alimentación y dietética del hospital de IESS de Machala." - Campuzano Vera, Andrea Belén (2013)
The Food and Dietetics Department of the Hospital of the Ecuadorian Social Security Institute (IESS) of Machala, has the need for a system which allows to know the number of dishes, according to the diet, which should be prepared by the staff of the Department and that in turn contributes to its distribution to the different rooms.